Molecular-genetic marking of Brassica L. species for resistance against various pathogens: achievements and prospects - F. A. Berensen; O. Yu. Antonova; А. M. Artemyeva (Вавиловский журнал генетики и селекции)
Cruciferous plants  belonging to the  genus  Brassica of the  Cabbage family (Brassicaceae) are cultivated  as vegetables, oilseeds and forage crops; they occupy one of the first places in Russia in the gross yield of vegetables. The yield of cabbage crops is adversely affected  by various pathogens, including bacterial, viral and fungal infections. The diseases such as black rot of cabbage (caused by the bacterium Xanthomonas campestris pv. campestris), downy mildew (caused by Hyaloperonospora parasitica), Turnip Mosaic Virus (TuMV) are not included  in the list of quarantine diseases  in the territory of the Russian Federation and Eurasian Economic Union (EAEU), but they can affect a part of the sown area and lead to significant (up to 100 %) crop losses. The development of cultivars resistant to these  pathogens is an important trend  in Brassica crop breeding in addition  to existing methods of agrotechnical and chemical protection. The development of molecular  marker techniques and marker-assisted selection  (MAS) methods makes it possible  to significantly increase  the efficiency of breeding resistant cabbage cultivars. The review contains  information on the currently  known  genes  and quantitative trait loci (QTLs) associated with resistance to black rot, downy mildew, and TuMV. Molecular mapping data for resistance genes  of Brassica species are shown. The molecular markers (RFLP, AFLP, SSR, EST, SNP, InDel, SLAF and others) closely linked to the resistance loci and SCAR-, STS- and dCAPS-markers derived from them  for molecular screening are listed. The use of the markers reviewed  to assess  the  Brassica accessions  and  lines can help  the  researchers in finding  sources  and  donors  of pathogen resistance of cabbage crops.